Biological Effect of the Surface Modification of the Fibrous Poly(L-lactic acid) Scaffolds by Radio Frequency Magnetron Sputtering of Different Calcium-Phosphate Targets; BioNanoScience; Vol. 7, iss. 1 - Goreninsky (Goreninskii) S. I. Semen Igorevich; Bogomolova N. N. Nataljya Nikolaevna; Malchikhina A. I. Alena Igorevna; Golovkin A. S. Aleksey Sergeevich; Bolbasov E. N. Evgeny Nikolaevich; Safronova T. V. Tatjyana Viktorovna; Putlyaev V. I. Valery Ivanovich; Tverdokhlebov S. I. Sergei Ivanovich (2017, 2017)
Title screen